Cloud-based expertise: Evaluating proficiency in SAP C/4HANA for predicting entrepreneurial readiness in startup businesses - Martono, S.; Yulianto, Arief; Wijaya, Angga Pandu; Plangsorn, Boonrat (Edelweiss Applied Science and Technology, 2024)
This study aims to examine the impact of digital competency on entrepreneurial alertness and entrepreneurial readiness. Digital competency, such as the use of SAP C/4HANA, plays a crucial role in business and entrepreneurship. The utilization of SAP C/4HANA for customer insights and sales automation is particularly important for startup companies. This research employs a quantitative approach, involving 193 respondents who are startup business owners. Data were collected from startup business owners in Indonesia. The data were analyzed descriptively using a digital competency map matrix to understand the skills in utilizing SAP C/4HANA. Additionally, inferential analysis was conducted to test the relationships between variables. The findings indicate that the finance and e-commerce sectors have widely adopted SAP C/4HANA. In the finance sector, leveraging data and cloud technologies is essential, while for e-commerce, data analytics and cybersecurity are paramount. The inferential analysis results show that digital competency has a positive direct effect on entrepreneurial alertness but not on entrepreneurial readiness. Entrepreneurial alertness fully mediates the effect of digital competency on entrepreneurial readiness. The implication of this research is to strengthen the adoption of digital technologies in business, highlighting the uneven utilization of SAP C/4HANA across different business sectors.